About the creative phenomenon of Maksud Shaikhzoda - Nizomitdinova Zulaykho Abduazizovna (Research Parks Publishers, 2021)
The article given information about the creative phenomenon of the Uzbek poet Maksud Shaikhzoda, reveals his creative path and artistic phenomenon.